Fate of four Different Classes of Chemicals Under Aerobic and Anaerobic Conditions in Biological Wastewater Treatment - Komolafe, Oladapo; Mrozik, Wojciech; Dolfing, Jan; Acharya, Kishor; Vassalle, Lucas; Mota, Cesar R.; Davenport, Russell (Frontiers in Environmental Science, 2021)
The removal mechanisms and extent of degradation of 28 chemicals (triclosan, fifteen polycyclic aromatic hydrocarbons, four estrogens, and eight polybrominated diphenyl ether congeners) in different biological treatment systems (activated sludge, up-flow anaerobic sludge blanket reactor (UASB) and waste stabilization pond (WSP)) was investigated to provide insights into the limits of engineered biological treatment systems. This was done through degradation experiments with appropriate controls in static reactors under aerobic and anaerobic conditions. Estrogens showed higher first order degradation rates (0.1129 h-1) under aerobic conditions with activated sludge inocula followed by low molecular weight (LMW) PAHs (0.0171 h-1), triclosan (0.0072 h-1), middle (MMW) (0.0054 h-1) and high molecular weight PAHs (HMW) (0.0033 h-1). The same trend was observed under aerobic conditions with a facultative inoculum from a WSP, although at a much slower rate. Biodegradation was the major removal mechanism for these chemicals in the activated sludge and WSP WWTPs surveyed. Photodegradation of these chemicals was also observed and varied across the group of chemicals (estrogens (light rate = 0.4296 d-1; dark = 0.3900 d-1) degraded faster under light conditions while reverse was the case for triclosan (light rate = 0.0566 d-1; dark = 0.1752 d-1). Additionally, all the chemicals were resistant to anaerobic degradation with UASB sludge, which implies that their removal in the UASB of the surveyed WWTP was most likely via sorption onto solids. Importantly, the first order degradation rate determined in this study was used to estimate predicted effluent concentrations (PECs). The PECs showed good agreement with the measured effluent concentrations from a previous study for these treatment systems.